The Body : A Very Short Introduction - Shilling, Chris (New York Oxford University Press, 2016)
In this introduction, Chris Shilling considers the social significance of the human body, and the importance of the body to individual and collective identities. He examines how bodies not only shape but are shaped by the social, cultural, and material contexts in which humans live.
Include Illustrations, References and Index
Keywords: Human body--Social aspects